Peptide partitioning properties from direct insertion studies - Ulmschneider, Martin B.; Smith, Jeremy C.; Ulmschneider, Jakob P. (Biophysical journal, 2010)
Partitioning properties of polypeptides are at the heart of biological membrane phenomena and their precise quantification is vital for ab-initio structure prediction and the accurate simulation of membrane protein folding and function. Recently the cellular translocon machinery has been employed to determine membrane insertion propensities and transfer energetics for a series of polyleucine segments embedded in a carrier sequence. We show here that the insertion propensity, pathway, and transfer energetics into synthetic POPC bilayers can be fully described by direct atomistic peptide partitioning simulations. The insertion probability as a function of peptide length follows two-state Boltzmann statistics, in agreement with the experiments. The simulations expose a systematic offset between translocon-mediated and direct insertion free energies. Compared to the experiment the insertion threshold is shifted toward shorter peptides by ∼2 leucine residues. The simulations reveal many hitherto unknown atomic-resolution details about the partitioning process and promise to provide a powerful tool for urgently needed calibration of lipid parameters to match experimentally observed peptide transfer energies.